Chronic dissection aneurysm of the aorta: clinical and pathologic study - Kuzyk, Yu. I.; Sira, O. O.; Beshley, D. M.; Fadeichuk, N. V. (Ukrainian Journal of Cardiovascular Surgery, 2019)
An analysis of the clinical case of chronic dissection aortic aneurysm (DAA) in a 47-year-old man was conducted. Diagnosis of chronic DAA type A for Stanford is established at CT angiography of the thoracic and abdominal aorta with proven contrast enhancement. The operation of supracoronary prosthetics of the ascending department of the aorta was performed with full root method. During surgery, a chronic RAA of the ascending aorta with a diameter of about 5.5 cm was detected. The aorta was enlarged in the area of the root, whereas at the point of transition into the arc was of ordinary diameter. The aortic valve was three-lobed with signs of slight dilation of the fibrous ring. The ascending aorta was circularly mobilized and excised 1.0 cm above the coronary artery cells. The organized thrombus from the false lumen from the lateral wall of the ascending aorta (from the side of the superior vena cava) was removed. A proximal anastomosis was applied between the vascular prosthesis and the ascending aorta with a telescopic double continuous suture. Subsequently, a distal ascending aorta 1.5 cm below the shoulder-main trunk was dissected. Therefore, a distal anastomosis was applied between the distal ascending aorta and the vascular prosthesis with a telescopic double continuous suture. The postoperative period was satisfactory. On the 8th day of the postoperative period the patient was in a satisfactory condition discharged home. Pathomorphological examination of the operating material revealed segmental hyperplasia of the media with focal mucoid swelling, multiple cystic cavities, diffuse-focal fibrosis. The cavity of the dissection looked like a “two-stemmed” (two-channel) lumen, located on the border of adventitia and media, was filled with blood clots with the spread of hemorrhagic infiltration into the peri-adventitious fat. The new pseudocanal contained blood clots and fresh blood clots, and the old one was completely covered with endothelium with neointima formation. The aortic architecture is completely broken, the division into layers was absent. In the section of the irregular canal, the formation of a two-layer structure was observed – neointima, which differed from the intima of the true lumen of the aorta by the number of smooth muscle cells and heterogeneous accumulation of components of the extracellular matrix. In the middle layers, connective tissue remodeling of the aorta was detected in the form of chaotically located immature mesenchymal cells in combination with muscular and connective tissue hyperplasia, complete loss of elastic fibers, massive sclerosis of adventitia, and periadventitial layer. In sections of the aorta, out of stratification, its structure was preserved, there are signs of cystic medial necrosis. The revealed pathomorphological changes in the described case point to the processes of vascular remodeling, which explain the relative stability of DAA.